Pengaruh Rating dan Ulasan Pelanggan di E-commerce Terhadap Keputusan Pembelian Skincare Somethinc pada Konsumen di Prambon - Imamatuz Zakiyah; Afifatus Sholikhah; Ummi Lathifatus Sholichah; Nur Qomariyah; Nuriya Sinta Dewi; Heni Nur Aidah; Sandy Bramantyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The evolution of technology has changed consumer behavior, especially in terms of online shopping in e-commerce, which has resulted in marketplace platform competition increasing significantly. This study aims to examine the effect of customer ratings and reviews on purchasing decisions on Somethinc skincare products in Prambon sub-district, Sidoarjo Regency. This research adopts quantitative methods. Data were analyzed using SPSS software. The results showed that there was a positive and significant influence between ratings on purchasing decisions, as well as customer reviews also showed a positive and significant influence on purchasing decisions for Somethinc products in e-commerce.